(untitled) (Zoological Records and Reviews, 2025)
Biodiversity and zoological research stand at a pivotal juncture: the convergence of unprecedented technological capabilities – whole-genome sequencing, artificial intelligence, Earth observation, autonomous sensor networks, and global open data infrastructure – with the most severe biodiversity crisis in human history and the most ambitious international conservation commitments ever adopted (Kunming-Montreal Global Biodiversity Framework; EU Biodiversity Strategy 2030; Nature Restoration Law) creates both a mandate and an opportunity to transform the scope and impact of zoological science. This review synthesises insights from 158 forward-looking analyses and expert elicitation studies (2015-2025) to identify ten priority research directions for European biodiversity and zoological research in the 2025-2040 decade. Priority directions are evaluated across four dimensions – scientific transformativeness, conservation management impact, technological readiness, and current European research capacity – and ranked by composite priority score. The highest-priority directions identified are: (1) AI-enabled real-time biodiversity monitoring using integrated sensor networks; (2) functional genomics of climate adaptation for proactive conservation management; (3) mechanistic multi-stressor prediction frameworks transferable across species and systems; (4) rewilding ecology and trophic cascade quantification; and (5) One Health surveillance integrating wildlife, domestic animal, and human disease monitoring. Structural barriers – taxonomic expertise erosion, funding cycle mismatches, open data gaps, and the research-policy translation deficit – are analysed alongside institutional solutions. A proposed European Zoological Research Agenda 2025-2040 aligns the ten priority directions with EU Horizon Europe programming, national research council priorities, and EU biodiversity policy implementation requirements.